Microbial Dysbiosis: Rethinking Disease in Marine Ecosystems - Egan, Suhelen; Gardiner, Melissa (Frontiers in Microbiology, 2016)
With growing environmental pressures placed on our marine habitats there is concern that the prevalence and severity of diseases affecting marine organisms will increase. Yet relative to terrestrial systems, we know little about the underlying causes of many of these diseases. Moreover, factors such as saprophytic colonizers and a lack of baseline data on healthy individuals make it difficult to accurately assess the role of specific microbial pathogens in disease states. Emerging evidence in the field of medicine suggests that a growing number of human diseases result from a microbiome imbalance (or dysbiosis), questioning the traditional view of a singular pathogenic agent. Here we discuss the possibility that many diseases seen in marine systems are, similarly, the result of microbial dysbiosis and the rise of opportunistic or polymicrobial infections. Thus, understanding and managing disease in the future will require us to also rethink definitions of disease and pathogenesis for marine systems. We suggest that a targeted, multidisciplinary approach that addresses the questions of microbial symbiosis in both healthy and diseased states, and at that the level of the holobiont, will be key to progress in this area.